Efektivitas Penggunaan Quizizz sebagai Media Penilaian Hasil Belajar Mahasiswa Tadris IPA pada Mata Kuliah Kimia Pangan - Imranah, Imranah; Kasman, Risqah Amaliah (Chemistry Education Review (CER), 2023)
This study aims to determine the effectiveness of using quizizz as a medium for assessing learning outcomes for Tadris IPA students in the Food Chemistry course. The research method used is a descriptive method with a quantitative approach. The subjects in this study amounted to 22 students. Data collection used a test instrument in the form of 20 multiple-choice questions. The analysis technique is in the form of inferential statistics which is processed using SPSS 25. Based on the research, the results show that the value of Sig. (2-tailed) of 0.999 > 0.05 at a significant level of 0.05. This shows that Ho is accepted or H1 is rejected, which means that the use of Quizizz is effective as a medium for assessing the learning outcomes of Tadris IPA students in the Food Chemistry course.